Are there structural alterations in the enamel organ of offspring of rats with alloxan-induced diabetes mellitus? - Silva-Sousa Yara Teresinha Corrêa; Peres Luiz Cesar; Foss Milton César (Fundação Odontológica de Ribeirão Preto, 2003)
Enamel hypoplasia is the most common developmental defect of human teeth that may be seen in deciduous teeth of babies born to diabetic women. In the present experimental study, we analyzed the enamel organ of the mandibular incisors of the offspring of rats with alloxan-induced diabetes. By light microscopy, no alterations could be found in the enamel organ of rats born to diabetic mothers compared to normal ones, except in one case. In contrast, significant differences were detected with computer-aided morphometry. In the rats born to treated and untreated diabetic mothers, there was thinning of the enamel matrix and of the ameloblasts and the nuclear area of the latter was smaller. In the rats born to treated diabetic mothers, the nuclei of the ameloblasts were more elliptical and there was enlargement of the interstitial area of the stellate reticulum. These results indicate that there are structural defects in the enamel organ of rats born to mothers with alloxan-induced diabetes which could induce the enamel hypoplasia observed by scanning electron microscopy and which may reflect the metabolic alterations seen in this condition. Future studies are needed to determine whether these effects are transitory or permanent.